DETERMINING PRIORITIES AND DRIVERS FOR THE DEVELOPMENT OF THE LOGISTICS POTENTIAL OF WATER TRANSPORT OF UKRAINE IN THE CONTEXT OF GEO-ECONOMIC CHANGES - SANZHAREVSKYI, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines key aspects of the development of the logistics potential of water transport in Ukraine in the context of modern geo-economic changes caused by military aggression, restructuring of global supply chains and increasing environmental requirements. The main challenges of the industry are identified, including the destruction of port infrastructure, blockade of seaports, change of trade routes, increasing transportation costs due to the energy crisis and the complication of customs procedures due to sanctions. Particular attention is paid to the negative impact of these factors on the functioning of the transport and logistics system and the country’s export potential. The prospects for the modernization of water transport through the introduction of innovative technologies, digital transformation of logistics processes and the transition to environmentally friendly solutions are analyzed. The feasibility of developing multimodal transportation, automation of port operations and integration of Ukraine into global logistics networks is considered. The study emphasizes the need to create a modern roadmap for the development of water transport, which includes investments in port infrastructure modernization, dredging, stimulation of public-private partnerships and implementation of international environmental standards. The importance of international cooperation in the restoration and development of the industry is emphasized, including attracting international technical assistance, creating joint investment projects and integration into European transport corridors. State support should play a key role in creating favorable conditions for investment, introducing incentives for digitalization of processes and forming a regulatory framework that will contribute to the harmonization of transport policy with international standards. Strategic directions for the development of water transport in Ukraine are proposed, aimed at restoring the economic potential of the industry, its sustainable development and ensuring the competitiveness of Ukrainian goods in international markets. The introduction of innovations, compliance with environmental requirements and active international cooperation will contribute to the country’s economic growth, its integration into global logistics systems and the formation of a modern transport infrastructure.